Otology/Neurotology recommendations – Choosing Wisely campaign - Andrew K. Ma; Julian Nedzelski; Joseph Chen; Trung Le; Paul Mick; Jane Lea; David Morris; Margaret Aron; Sumit Agrawal; Lorne Parnes; Tamara Mijovic; Vincent Lin; et al. (Journal of Otolaryngology - Head and Neck Surgery)
Abstract The Choosing Wisely Canada Campaign aims to raise awareness amongst physicians and patients regarding unnecessary tests and treatment. The otology/neurotology subspecialty group within the Canadian Society of Otolaryngology – Head & Neck Society developed a list of five common otologic presentations to help physicians deliver high quality effective care: (1) Don’t order specialized audiometric and vestibular testing to screen for peripheral vestibular disease, (2) Don’t perform computed tomography or blood work in the evaluation of sudden sensorineural hearing loss, (3) Don’t perform auditory brain responses (ABR) in patients with asymmetrical hearing loss, (4) Don’t prescribe oral antibiotics as first line treatment for patients with painless otorrhea associated with tympanic membrane perforation or tympanostomy tube, and (5) Don’t perform particle repositioning maneuvers without a clinical diagnosis of posterior canal benign paroxysmal positional vertigo.